La quimera Del origen (de Borges a Chartier) / The orgin’s chimera (from Borges to Chartier) - Pasero, Carlos Alberto (Revista de Letras, 2007)
O artigo analisa a relação intertextual entre o conto de Borges, “Pierre Menard, autor del Quijote”, e o estudo de Chartier sobre as origens culturais da Revolução Francesa. O trabalho de Chartier relaciona-se do ponto de vista historiográfico com “Pierre Menard...” e estabelece um jogo de analogias que o aproxima da sugestiva teoria da historia de Borges. The article analyzes the intertextual relation between the tale by Borges, “Pierre Menard, autor del Quijote” and Chartier’s study on the cultural origins of the French Revolution. Chartier’s work is related to “Pierre Menard, autor del Quijote” from a historiographic point of view, establishing a set of analogies that draws it near Borges’ suggestive theory of history.